Gender differences in responsible sexual behaviour of in-school adolescents (2013)
There are indications that gender influences involvement in risky activities including sexually risky behaviour. The present study therefore sought to explore gender differences in responsible sexual behaviour among in-school adolescents. Using a cross-sectional survey design, two hundred and fifty In-School adolescents drawn from Secondary Schools in Ondo State, South West Nigeria participated in the study. Participants were made up of 97 (38.8%) males and 153 (61.2%) females, with ages ranging from 11 to 23 years with a mean of 15.5 and standard deviation of 2.7. A structured questionnaire containing two sections was utilized for data collection. Section A tapped demographical information such as age, sex, and religion while Section B is the sexual behaviour scale developed by Oluwatelure, (2011). The Cronbach alpha of the scale in the present study was .90. T-test of independent means was used to test the hypothesis. Result revealed significant gender difference in responsible sexual behaviour ( t (246) = -4.08; p<.05). Female adolescents were found to show significantly higher positive disposition to responsible sexual behaviour than male adolescents. It is thus recommended that intervention be put in place to infuse the virtue and values of responsible sexual behaviour in males while effort should be made to sustain and improve on responsible sexual behaviour among females.